The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1507/endocrj.ej17-0256
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide and renal function in Japanese patients with type 2 diabetes mellitus: The Dogo Study

Abstract: THE LEADING CAUSE OF THE DEATH among patients with renal dysfunction is cardiovascular diseases [1], and the importance of the interaction between the heart and kidneys is widely note [2]. Plasma B-type natriuretic peptide (BNP) releases from the ventricles in response to hemodynamic stress, and BNP is one of the predictive markers for cardiovascular events [3,4].Among patients with type 2 diabetes mellitus, sev- Abstract. Among patients with type 2 diabetes mellitus, the association between B-type natriuretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In our study, we found that BNP, IL-10, and TGF-β increased significantly across albuminuria categories. Our results are in agreement with other cohort studies reporting a tight, positive correlation between BNP and albuminuria, regardless of GFR in diabetics, [37,38]. In another study enrolling 1000 primary care patients, BNP was independently associated with GFR, regardless of structural kidney injury [39].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that BNP, IL-10, and TGF-β increased significantly across albuminuria categories. Our results are in agreement with other cohort studies reporting a tight, positive correlation between BNP and albuminuria, regardless of GFR in diabetics, [37,38]. In another study enrolling 1000 primary care patients, BNP was independently associated with GFR, regardless of structural kidney injury [39].…”
Section: Discussionsupporting
confidence: 93%
“…Of the laboratory parameters with less than the required 400 baseline values, it is of interest that brain natriuretic peptide, C-reactive protein and urinary alpha-1 microglobulin were greater than the ULN in more than 10% of the subjects as according to literature these three laboratory biomarkers have been shown to be elevated in individuals with diabetes. 12,13 This data, although with less than 400 subjects, may, therefore, be useful in better understanding the more currently esoteric laboratory parameters. The 28% of laboratory parameters being potentially different from the HVRR further support the pilot study and general medical judgement that it is not uncommon for laboratory parameter values to be different from the HVRR in patient populations.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, it has been reported that inflammatory markers related to cardiovascular disease did not significantly differ in subjects with and without MetS [ 22 ]. On the other hand, albuminuria in diabetics may be associated with comorbidities due to diabetes mellitus [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%